Կապի հնչյունական, բառային և քերականական դրսևորումները Գորիսի բարբառում - Քումունց, Մհեր; Բաղդասարյան, Մանանա (ՀՀ ԳԱԱ ԼԻ հրատ.)
In this article, we studied the Prepositions of the Goris dialect. We carried out the work using the comparative and analytical method, comparing the dialect connections with the corresponding forms of literary Armenian. We have presented the prepositions according to inflection, bringing live dialectal examples from the Goris dialect. Dialects are living and uncontrollable options in which prepositions play an important role. Unfortunately, the connections of the Goris dialect have not yet been sufficiently studied, and there is a need to verify this grammatical system.There are no studies presenting the origin, composition and historical change of Goris dialect connections. During the historical development of the dialect, these parts of speech have also changed. Most of them, due to little use, have left the functional layer of the dialect over time and aren't applicable to this day. However, many prepositions have undergone changes through assimilation, phonetic deviations and general radical changes. The article also presents different pronunciation forms of prepositions according to the dialect units of the Goris region. We have tried to find out the origin of a number of connections, found the sources of their origin, according to that we have distinguished borrowed connections, as well as connections with native and ancient Armenian origins. В этой статье мы рассмотрели предлоги и послелоги в Горисском диалекте. Мы провели работу сравнительным и аналитическим методом, сравнивая диалектные связи с соответствиями в литератур-ном армянском языке. Мы представили связи по спряжению, приведя живые примеры диалекта из Горисского диалекта. Диалекты-это варианты с живым и неконтролируемым состоянием, и связи выполняют в них важную функцию. К сожалению, до сих пор связи Горисского диалекта изучены недостаточно, и существует потребность в проверке этой грамматической системы. Нет исследований, представляющих происхождение, состав и историческое изменение диалектных связей Гориса. В ходе исторического развития диалекта части этой речи также были изменены. Многие из них со временем выпали из функционального слоя диалекта из-за небольшого использования и до сих пор неприменимы. Однако многие союзы претерпели изменения в результате присоединения, произошли фонетические отклонения и общие радикальные изменения. В статье также представлены различные формы произношения союзов в соответствии с диалектными единицами Горисского района. Мы попытались выяснить возникновение ряда связей, нашли истоки их происхождения, соответственно выделили заимствованные связи, такие как связи, имеющие исконно армянское и древнеармянское происхождение.
Keywords: Բարբառագիտություն